Water Resources as the Material Basis for Further Strategic Development of the Republic of Kazakhstan - KUSMAMBETOV, Kuanysh Daniyarovich; SULEIMENOVA, Saule Zhussupbekovna (Journal of Environmental Management and Tourism; Vol 13 No 1 (2022): JEMT, Volume XIII, Issue 1(57), Spring 2022DO - 10.14505/jemt.v13.1(57).08, 2022)
Of all various kinds of natural resources that provide vital activity of all kinds of living organisms, people, society and state, the most important are water resources without the presence of which it is impossible not only for human life itself but also for the whole environment. Waters are the most important components of the environment, renewable, limited and vulnerable natural resources. They are used and protected as the basis of life and activities of the peoples living on the territory of the Republic of Kazakhstan, provide economic, social, environmental well-being of the population, the existence of fauna and flora (Fedtsov, V.G., Fedtsova, A.V. and Ezhov, Y.A. 2005). Occupying the 9th place in the world in terms of the size of its territory, the Republic of Kazakhstan due to its geographical location, local climate, dependence on transboundary water resources and other reasons, belongs to the category of one of the poorly water-secured regions of the globe. This fact entails the need to organize the processes of the most careful attitude to water resources, the legal provision of its rational use and all-round protection from pollution, littering and depletion, in order to ensure water security not only for the citizens of the Republic of Kazakhstan, but also for all mankind.